MODERNISASI PERLINDUNGAN HUKUM TERHADAP KONSUMEN LOKAPASAR TOKOPEDIA DI INDONESIA - DARWIS MANURUNG (JURNAL AKTA YUDISIA, 2025)
The rapid development of digital technology has significantly increased e- commerce transactions in Indonesia. However, this growth has not been matched by adequate legal protection for consumers. This paper aims to examine the effectiveness of consumer protection in e-commerce transactions based on existing Indonesian legislation. The method used is a normative approach with legal analysis of the Consumer Protection Law and relevant e-commerce regulations. The findings reveal legal gaps, weak enforcement, and low consumer literacy as major challenges in upholding consumer rights. Therefore, regulatory reform, stronger government and business sector involvement, and public education are necessary to ensure legal certainty and justice for consumers in the digital era.